Effects of age, gender, frailty and falls on spatiotemporal gait parameters: a retrospective cohort study - ROCHE, Nicolas; CHORIN, Frédéric; GERUS, Pauline; DESHAYES, Maxime; GUERIN, Olivier; ZORY, Raphael (European journal of physical and rehabilitation medicine, 2021)
Many studies have explored spatial and temporal gait parameters in the elderly, and showed that frailty status, fall history, age, and gender may individually strongly influence these parameters. However, it appears necessary to investigate the confounding factors more deeply in order to better know the specific role of each of these factors impacting the evolution of gait with the increase of age. The aim of the present study was to determine the influence of frailty status, fall history, age and gender on spatiotemporal gait parameters. We hypothesized that frailty was the factor that most influence gait parameters. The present is a monocentric retrospective study. This is a monocentric retrospective study performed at Nice University Hospital Center on older out-patients. Older adults were included in the study. This study explored for the first time how frailty status, age, gender and history of falls impact the multiple spatiotemporal parameters of gait using linear mixed models (LMM). 479 older adults (360 women and 119 men; 213 non-frail, 228 prefrail and 38 frail; aged from 65 to 94 years; 403 non-fallers and 73 fallers). Frailty status explained fully: 1) the gait speed; 2) the cadence; 3) the initial double contact (DS1); 4) the percentage of the single support phase; 5) the final double contact (DS2); and VI) the percentage of the swing phase of the gait cycle. The results of this study allowed a deeper understanding of the confounding factors since LMM highlighted the importance of frailty status for explaining all the spatiotemporal gait parameters. These results showed that clinical intervention should focus on reducing frailty status to improve gait. It is also interesting to note that a history of falls explains none of the spatiotemporal gait parameters which suggests that it may be possible to improve gait in all frail subjects irrespective of their history of falls.